Komunikasi BENTUK KOMUNIKASI POLITIK RETORIKA POLITIK: BENTUK KOMUNIKASI POLITIK RETORIKA POLITIK - farhan yut wijaya (Program Studi Ilmu Komunikasi Universitas Mataram, 2023)
ABSTRACT Rhetoric was prepared to be a lecture material and reference book, especially for students andinterested people who want to deepen their knowledge and apply it in formal and nonformal situations. lPolitical rhetoric is an important tool for political leaders and actors in shaping public opinion, building images, and influencing political decisions. Rhetoric according to Aristotle is the ability to express something and by communicating it rhetoric can have the effectof persuading the listener. The analysis of political rhetoric in this article is that political rhetoric has seven approaches. Through case studies of recent political events, this article alsoidentifies the history of political rhetoric. In addition, this article evaluates political rhetoric approaches in the democratic process. The importance of understanding political rhetoric is notonly limited to the context of winning elections, but is also closely related to how political leaders build relationships with the public and maintain support during their term of office. Byunderstanding political rhetoric, people can be more critical in evaluating the political messages conveyed and have a deeper understanding of the political dynamics that influence their lives. Keywords: Politics, Rhetoric, Political rhetoric